2016
DOI: 10.1021/acsami.6b08536
|View full text |Cite
|
Sign up to set email alerts
|

One-Step and Templateless Electropolymerization Process Using Thienothiophene Derivatives To Develop Arrays of Nanotubes and Tree-like Structures with High Water Adhesion

Abstract: Here, we report for the first time the possibility to obtain not only arrays of nanotubes but also tree-like structures with high water adhesion using a one-step and templateless electropolymerization process. Using thienothiophene derivatives, particularly thieno[2,3-b]thiophene (Thienothiophene-1) and thieno[3,2-b]thiophene (Thienothiophene-2), we demonstrate this surface fabrication in organic solvent (dichloromethane) and without any surfactants. The formation of nanotubes is due to the stabilization by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Monomer synthesis : The strategy used here to obtained substituted NaphDOT was inspired than that reported for substituted PheDOT . The monomers were obtained in five steps from 2,3‐naphthalenediol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monomer synthesis : The strategy used here to obtained substituted NaphDOT was inspired than that reported for substituted PheDOT . The monomers were obtained in five steps from 2,3‐naphthalenediol.…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, we demonstrated the possibility to prepare arrays of vertically aligned nanotubes in organic solvent (dichloromethane, for example) and without any surfactant . Here, trace water present naturally in organic solvent is sufficient to produce gas bubbles . In this process, the role of the monomer is fundamental because it has also to play the role of the surfactant that means it has to stabilize the gas bubbles sufficiently long to allows the polymerization of the polymer around the bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…One of the greatest advantages of electropolymerization is that it permits the formation of varied surfaces morphologies, including nanosheets, nanofibers, nanospheres, cauliflower‐like structures, and even smooth surfaces with tunable wettability. Although many monomers present high stability to the electrochemistry parameters, the morphology of others may be easily changed by adjusting the electrolyte or temperature, for example …”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was demonstrated that arrays of vertically aligned nanotubes with extremely high water adhesion could be obtained by using an appropriate monomer and electrochemical conditions, without a template, . More precisely, the presence of trace water in solution could lead to the formation of different gases (O 2 and/or H 2 ) following the potential ranges used during polymerization and, as a consequence, highly influence the surface morphology and hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…Of note among this type of surface development is the electrochemical polymerization of aromatic monomers to form conducting polymer films, which is a reliable, cost‐effective, and easily used technique. Attesting to the versatility of this technique is the wide variety of surface morphologies previously demonstrated with this approach including nanofibers, globular agglomerates, and nanotubes . Various functional monomer classes, including pyrroles, anilines, pyrenes, and thiophenes have been explored for this purpose.…”
Section: Introductionmentioning
confidence: 99%